1570. Infectious Disease (ID) Complications in Immunocompromised (IC) Patients with Cancer Post-Hurricane Harvey at a Comprehensive Cancer Center in 2017. (26th November 2018) - Dishner, Emma; Adachi, Javier
Abstract: Background: During 2017, Houston had the most destructive flood-related disaster in recent history due to Hurricane Harvey. Afterward, educational material with information of possible ID problems was provided to all healthcare workers. Methods: Prospective surveillance of flood-related ID complications in IC cancer patients. During the 60 days post-Harvey, we monitored referrals to the ID service at MDA Cancer Center. We used the following definitions: Type of exposure: direct to flood water, direct to flooded structures, and others indirect (i.e., prophylaxis). Association risk: "Yes" (direct exposure), "No" (asymptomatic, no exposure, or infection noted prior) and "Probable" (lack of records to establish correlation). Types of infections were classified as soft tissue, gastrointestinal, respiratory, IV line associated or fever. Recommendations were noted including types of antibiotics, vaccinations, or imaging. Results: A total of 36 cases were referred to our department. Fifty-six percent had exposure to flood-water with/without exposure to structures, 33% to structures only and 11% were other (Figure 1). Regarding the association of an ID problem to flood-exposure, we found an equal distribution of 39% with an association and 39% with a probable association, and the remaining 22% with no association (Figure 2). Of the infections, the majority of infections were respiratory (42%) or soft tissue (31%) (Figure 3). There was a trend of broader antimicrobial coverage for water associated bacteria and mold infections. Only six immunizations recommendations were attained. Conclusion: To our knowledge this is the first and largest study of ID complications in IC cancer patients following a natural disaster in medical literature. Our active surveillance showed a lower number of disaster related ID complications than anticipated, possibly because of difficulty determining exposure and underreporting of infections despite active education. Due to individual immunosuppression and exposure, there was variety of recommendations (antimicrobials, studies, or vaccinations). In the event of a weather disaster, we are developing a standard triage survey regarding type of exposure and impact, and also a process for effective immunizations. Disclosures: J. Adachi, Merck: Grant Investigator, Research grant